LEADERSHIP DALAM PENDIDIKAN: ANALISIS RISET DAMPAK PADA KINERJA GURU DAN BUDAYA MUTU PENDIDIKAN DI SEKOLAH TAHUN 2020 – 2026 - Faizah, Fathiyyatil; Rohayati; Novia Hariyanti, Feny; Monica Hetharia, Riesta; Rokhman, Fathur; Oktarina, Nina; Tjokro, Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the impact of transformational leadership on teacher performance and the culture of educational quality in schools based on empirical research published between 2020 and 2026. Using a library research method, this article synthesizes findings from various academic databases. The results indicate that transformational leadership significantly improves teacher motivation, professionalism, and innovation, particularly during and after the COVID-19 pandemic. School principals acting as transformational leaders play a central role in fostering a sustainable quality culture, enhancing digital adaptation, and building positive school climates. However, challenges remain regarding contextual differences, resource availability, and research gaps, including the need for longitudinal and mixed-methods studies. This article confirms that transformational leadership remains a highly relevant and effective approach for improving educational quality in contemporary school settings.